Online Communication versus Face-to-Face Interaction: the Effect of Chatting Communication on Iranian EFL Learners' Oral Performance - Samad Mirza Suzani (Universitas Islam Negeri Walisongo Semarang, 2021)
This study aimed to investigate the impact of chatting communication on Iranian EFL learners' oral performance. To this end, the author randomly selected fifty 17-to-18-year-old male Iranian EFL learners attending Top Notch communicative classes in language institutes in Shiraz. First, they applied the Oxford Placement Test as a proficiency test to homogenize learners, and then the learners were divided into experimental and control groups (n = 25 in each group). Both groups had a pretest to estimate their oral performance before applying treatment. The experimental group received instruction and materials via online context as treatment. However, the participants in the control group just received instruction via traditional teaching methods in the class. Finally, both groups had a post-test to measure the effect of treatment on their oral performance. The mean and standard deviation were calculated for two groups In the data collection and analysis, a paired samples t-test was conducted. Based on the results, between the two groups, there was a substantial disparity in terms of oral presentation skills., and the experimental group learners outperformed the control group's learners. The findings can be helpful for teachers to find practical ways to develop students' skills and their incentives.